UPAYA MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN MENGGUNAKAN MEDIA KARTU SUKU KATA DI SEKOLAH DASAR - Nevi Novelita; Neviyarni; Irdamurni (STKIP Subang, 2023)
Reading has a big effect on students' ability to accept subject matter, especially text-based learning, students who are unable to read well will have difficulty participating in learning activities for all subjects. Children's initial reading ability is the child's ability to master reading techniques and understand the contents of the reading well. One of the learning methods to improve children's early reading skills is to use syllable media. The method used in this research is literature research (library research). Beginning reading ability in children is focused on six stages of ability aspects, namely: (1) Ability to read symbols, (2) Ability to read letters, (3) Ability to read types of vowel and consonant sounds, (4) Ability to name letter sounds, (5) Ability reading syllables, and (6) Ability to read words. Media Syllable cards can help teachers achieve instructional goals because apart from being cheap and easy to obtain media, they can also increase student activity. In addition, students' knowledge and understanding becomes wider, clearer, and not easily forgotten